Religious Holiday Anomaly : Evidence from the Indian Equity Market - Sing, Nang Biak; Ropuii, Lal; Singh, Rajkumar Giridhari (Indian Journal of Finance, 2025)
Purpose : Investments in financial markets are intended to provide higher returns. However, this complex market is influenced by a large number of events, creating a disruptive effect on price movements and potentially leading to market distortions. In this context, the present study examined the persistence of seasonal anomalies during religious holidays in the Indian stock market. Design/Methodology/Approach : The model employed symmetric and asymmetric GARCH models. The symmetric GARCH model captured volatility clustering, whereas the asymmetric PGARCH model included long-memory and leverage effects. Additionally, a robustness test using the ARIMAX model was conducted to assess temporal pre- and post-holiday effects. The period from July 2020 to December 2022 was selected based on the BSE Sensex and NSE Nifty 50 indices. Findings : The results revealed that Christian and Jainist holidays showed significant pre-holiday returns, while Hindu and Sikh holidays showed stronger post-holiday return effects. No significant effects were found for Islamic holidays. Volatility clustering patterns exhibited distinct holiday-specific market characteristics. Finally, the robustness test confirmed the persistence of the time-varying pre- and post-religious holiday effects. Practical Implications : Market participants could enhance their profit trading strategy by carefully considering the timing and position of religious holidays. Regulatory measures could enhance the limits of circuits around major religious holidays to prevent excessive volatility and market manipulation. Originality/Value : To the best of our knowledge, no previous study has examined the market impact of mandated religious observations. This study added value to the behavioral finance literature on how religious beliefs influence stock market behavior.